The Role Of Public Relations Management In Building Public Trust In Islamic Schools - Susilo Surahman (Journal of Innovative and Creativity, 2026)
Public trust is a crucial social capital for the sustainability and competitiveness of educational institutions, including Islamic schools, which currently face challenges of perception, stereotypes, and demands for transparency amidst the dynamics of modern society. In this context, public relations (PR) management plays a strategic role as a liaison between schools and both internal and external publics. This article aims to analyze the role of PR management in building and strengthening public trust in Islamic schools through systematic communication planning, implementing programs oriented towards information transparency, and evaluating ongoing relationships with stakeholders. This research uses a qualitative approach with literature study methods and descriptive analysis of various scientific sources, both national journals in Indonesian and international journals in English, to obtain a balanced and comprehensive perspective. The results of the study indicate that effective PR management in Islamic schools is characterized by the ability to convey the institution's identity positively, manage the school's image and reputation, and build participatory two-way communication with the community, parents, and the media. Furthermore, the integration of Islamic values ​​in PR strategies has been shown to strengthen moral legitimacy and increase public trust in a sustainable manner. This article emphasizes that successful public relations management depends not only on the technical aspects of communication but also on an institutional commitment to accountability, professionalism, and inclusive Islamic values. These findings are expected to serve as a conceptual reference for Islamic school administrators in designing adaptive public relations strategies oriented toward strengthening public trust.